2005
DOI: 10.1143/jjap.44.1661
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Field Emission Sites in a Single Multiwalled Carbon Nanotube by Lorenz Microscopy

Abstract: Emission sites were observed as bright spots near the tip end of a multiwalled carbon nanotube (MWNT) by means of Lorenz microscopy. The bright spots appeared above electric fields as electrons were emitted. A marked fluctuation was observed in the emission current above 20–30 µA, which was closely related to structural changes at the tip of the MWNT. The layers of the MWNT were peeled off during field emission and they functioned as the second emission sites for the concentration of electric field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…buckyball), SWCNT, scanning electron microscopy (SEM) image of chemical vapor deposition (CVD) grown array of MWCNT towers, and an important example of CNT-based application in electronic systems as a channel in a FET. The newly emerging CNT technology has been implemented in many new promising applications (Al-Rabadi, 2007, 2009aAmaratunga, 2003;Bonard et al, 2002;Cheng et al, 2004;Collins and Avouris, 2000;Collins et al, 2001;Derycke et al, 2001;Drexler, 1986;Fujieda et al, 2005;Jiao et al, 2003;Likharev, 2003;Tomanek et al, 2002). These applications include TVs that are based on the field emission of CNTs that consume much less power, are thinner, and have much higher resolution than the best plasmabased TVs available; nanocircuits based on CNTs such as CNT-based FETs that consume less power and are much faster than the available silicon-based FETs; carbon nanocoils that can be used as inductors in nanofilters and as nanosprings in nano dynamic systems; and CNT rings.…”
Section: Cnts Characteristics and Propertiesmentioning
confidence: 99%
“…buckyball), SWCNT, scanning electron microscopy (SEM) image of chemical vapor deposition (CVD) grown array of MWCNT towers, and an important example of CNT-based application in electronic systems as a channel in a FET. The newly emerging CNT technology has been implemented in many new promising applications (Al-Rabadi, 2007, 2009aAmaratunga, 2003;Bonard et al, 2002;Cheng et al, 2004;Collins and Avouris, 2000;Collins et al, 2001;Derycke et al, 2001;Drexler, 1986;Fujieda et al, 2005;Jiao et al, 2003;Likharev, 2003;Tomanek et al, 2002). These applications include TVs that are based on the field emission of CNTs that consume much less power, are thinner, and have much higher resolution than the best plasmabased TVs available; nanocircuits based on CNTs such as CNT-based FETs that consume less power and are much faster than the available silicon-based FETs; carbon nanocoils that can be used as inductors in nanofilters and as nanosprings in nano dynamic systems; and CNT rings.…”
Section: Cnts Characteristics and Propertiesmentioning
confidence: 99%
“…This could be attributed by changes in the morphology of the tip due to the process of field emission. It has been reported that during field emission the outer carbon rings of the CNT can become detached [37]. This would cause a sudden increase in the sharpness of the tip and thus create additional field enhancement.…”
Section: A Electrostatic Calculationsmentioning
confidence: 99%
“…In this article, the utilization of Carbon field emissionbased devices that realize a basic building block in modern synthesis known as the controlled switch [2,32] is presented, and the use of the presented Carbon field emission-based devices in three-valued 3D computations is also shown for the widely-utilized case of ternary Galois logic. In this new realization, the applied Carbon field-emission is obtained using carbon-based nanotubes [19,27] and carbonbased fiber nano-apex tips [11 -12, 25]. This article introduces concurrent processing using field emission-based lattice systems.…”
Section: Introductionmentioning
confidence: 99%